Online communities : designing usability, supporting sociability - Preece, Jenny, 1949- (John Wiley & Sons Ltd., 2000)
Developing online communities is not only for Internet entrepreneurs but for users with the widest variety of interests, backgrounds and motives for banding together. This text provides practical guidance.